Small scale farmers and resilience adaptive strategies to climate change in Kakamega county - Mulinya, C.; Ang'awa, F.; Tonui, Warkach K. (Researchgate, 2015)
Kakamega County is a rich agricultural area where various food and cash crops are grown. However, changes in climate coupled with declining soil fertility over the area have an impact on crop production, and hence affect food security especially among small scale farmers. On the basis of this scenario, this study sought to explore the existence and determine the characteristics of climate variability/change, assess its impact on small scale farmers and explain their resilience and adaptive strategies. The study adopted a descriptive survey design. Data from both primary and secondary sources were used. The latter included data collected from meteorological stations and was mainly rainfall and temperature data for a period of 46 years (1968-2014) to establish any existence and characteristics of climate variability/change in the study area. Primary data included Focal Group Discussions (FGDs), questionnaires and interview schedules administered to farmers to gain information on trends on crop production and adaptation strategies to climate change if any. Regression analysis was used in the study to establish the rainfall and temperature trends. Spearman rank correlation test was used to establish any existence of relationships between various variables under study. It was established that there were changes in rainfall amounts and temperature in the region. The rainfall amounts were having a negative trend of 3mm per annum, a sign of reduction over time, whereas temperatures had a negative trend of 0.04 0 C on yearly basis. Despite these changes in climate crop farmers had put in practice some adaptation strategies to cope with the changing trends, though they were faced with many challenges in trying to implement these strategies.
Keywords: Climatic Change; Adaptation Stategies; Small scale farmers